Cross-cultural pragmatics of political apologies: Face management and image restoration in public scandals - Lailiyah, Nur; Wijayanti, Farida Indri; Kurwidaria, Favorita; Areni, Galuh Kirana Dwi; Surtikanti, Monika Widyastuti (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study investigates the pragmatic dimensions of political apologies in the context of public scandals, with particular emphasis on face management strategies and image restoration efforts. Drawing upon Brown, et al. (2023) politeness theory and Benoit’s (2022) image restoration theory, this study analyzes 50 political apologies delivered by politicians from five democratic countries the United States, the United Kingdom, France, Japan, and Australia between 2013 and 2023. Data were collected from official transcripts, video recordings, and media coverage, and were examined through the lens of critical discourse analysis. The findings reveal significant variations in both linguistic and non-linguistic strategies. American politicians tend to emphasize personal responsibility and corrective actions. In the United Kingdom, apologies are more implicit, often centering on expressions of regret. French politicians frequently contextualize wrongdoing within broader socio-political discourses. In Japan, apologies typically involve profound gestures and expressions of shame. Meanwhile, Australian politicians often employ self-deprecating humor to diffuse tension. This study contributes to a cross-cultural understanding of face management in political discourse and highlights the importance of cultural intelligence in global crisis communication. The practical implications include guidelines for crafting culturally sensitive apologies to enhance the effectiveness of image restoration efforts for politicians in the aftermath of scandals.